Research of the range of medication for pulmonary hypertension pharmacotherapy in adults in the pharmaceutical market of Ukraine - A. V. Kabachna; I. S. Datsenko; V. S. Hulpa (Фармацевтичний журнал, 2021)
Pulmonary hypertension (PH) is a group of rare diseases, malignant in nature, without optimal treatment quickly lead to death. Such patients usually require expensive, continuous and lifelong treatment. Therefore, the study of the assortment structure of drugs used for the treatment of drugs in adults in the domestic market of medicines (drugs) is very relevant.